Bio-pesticidal, Antimicrobial, and Anti-inflammatory Potentials of n-Hexane Fraction of Zanthoxylum armatum DC and its Chemical Profiling - Baral, Janaki; Adhikari, Achyut (Journal of Nepal Chemical Society, 2024)
Zanthoxylum armatum DC, commonly known as toothache tree, is utilized for treating inflamed gums. The plant’s volatile constituent possesses a robust fragrance and contributes to its tangy taste. This study investigates the bioactivities, including bio-pesticidal, antimicrobial, and anti-inflammatory properties as well as the chemical profiling of the n-hexane fraction based on GC-MS analysis. The evaluated activities involve contact toxicity, microplate alamar blue assay, against three different insects, five bacteria, and seven fungi, and oxidative burst assay. The NIST library serves as a standard reference database for constituent identification. Remarkable insecticidal activities comparable to the standard drug permethrin were observed, particularly against Rhyzopertha dominica (100%), Tribolium castaneum (60%), and Sitophilus oryzae (50%). The fraction exhibited significant antifungal activity against Fusarium lini (85%) and notable inhibition against B. subtillis (67.27%) and S. aureus (65.25%). Potent anti-inflammatory effects were noted with an IC50 value of 11.2±1.9 μg/ml, equivalent to standard ibuprofen at various concentrations. GC-MS analysis identified twenty compounds, with major ones including trans-13-octadecenoic acid (36.08%), cis-9 hexadecenoic acid (18.66%), and 2-propenoic acid 3 phenyl methyl ester (11.08%). The diverse bioactivities observed may be attributed to the varied nature of compounds such as polyunsaturated fatty acids and their oxides. This research revealed the potential of Z. armatum as a potential bio-pesticide, anti-inflammatory, and antimicrobial agent.